1998
DOI: 10.1029/97rs02747
|View full text |Cite
|
Sign up to set email alerts
|

Sea‐air and boundary layer temperatures measured by a scanning 5‐mm‐wavelength radiometer: Recent results

Abstract: In atmospheric studies, low-level temperature gradients are also important to meteorology and air pollution studies. The gradients can be determined 291

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Assuming that the instrumental random errors for the MWSR, the IRSR, and the radiosonde sensors are uncorrelated, we are able to say that the experiment achieved a RMS retrieval accuracy as low as 0.21 K for air temperature profiles up to 500 m and 0.20 for air/ sea temperature differences, with the last decreasing to 0.11 K for nighttime measurements. These values validate the accuracy estimated by previous investigators Westwater et al, 1998;Shaw et al, 2001], who considered a single scanning radiometer. These values also meet the accuracy required by marine boundary layer models to study the parameterization of atmosphere-ocean interactions [Schluessel et al, 1990;Fairall et al, 1996;Wick et al, 1996].…”
Section: Comments and Conclusionsupporting
confidence: 89%
See 1 more Smart Citation
“…Assuming that the instrumental random errors for the MWSR, the IRSR, and the radiosonde sensors are uncorrelated, we are able to say that the experiment achieved a RMS retrieval accuracy as low as 0.21 K for air temperature profiles up to 500 m and 0.20 for air/ sea temperature differences, with the last decreasing to 0.11 K for nighttime measurements. These values validate the accuracy estimated by previous investigators Westwater et al, 1998;Shaw et al, 2001], who considered a single scanning radiometer. These values also meet the accuracy required by marine boundary layer models to study the parameterization of atmosphere-ocean interactions [Schluessel et al, 1990;Fairall et al, 1996;Wick et al, 1996].…”
Section: Comments and Conclusionsupporting
confidence: 89%
“…However, Trokhimovski et al [1998] suggested that this technique results in an air/sea temperature difference retrieval accuracy better than 0.1 K, based on forward model simulations. Westwater et al [1998] found that microwave scanning radiometry yields rms accuracies of the order of 0.4 K for air/sea temperature difference when compared with nonscanning infrared measurements.…”
Section: Introductionmentioning
confidence: 99%
“…D'Auria et al (1998) used 19, 35 and 85 GHz frequency observations to study cloud properties and to generate a database of cloud genera useful for radiative-transfer modelling. Westwater et al (1998) deployed a scanning MWR operating at a frequency of 5 mm (60 GHz) to study differences in boundary layer evolution over land and ocean. Their results showed the excellent agreement between atmospheric temperatures estimated by MWR and other measurements (meteorological towers and IR measurement).…”
Section: K Ramesh Et Al: Adaptive Neuro-fuzzy Inference Systemmentioning
confidence: 99%
“…In this paper we analyze only data which are supported by the meteorological and turbulent flux measurements. Figure 4 shows the difference between water skin and air temperature determined by a scanning 5 mm radiometer Westwater et al, 1998] and wind speed U and direction rpt• measured from FLIP. The time intervals of blimp measurements are indicated in Figure 4 by horizontal lines.…”
Section: Paper Number 1999jc900315mentioning
confidence: 99%